Reconceptualizing the archetypal trickster in Audre Lorde’s Zami: A new spelling of my name - Saber, Yomna (Journal of Lesbian Studies, 2015)
Carl Jung categorizes the trickster as a psychological archetype and sets certain parameters for it. This article examines Audre Lorde’s trickster Afrekete in Zami: A New Spelling of My Name (1982) and poses the question of how typically archetypal a Black, female, lesbian trickster can be. Lorde occupies an idiosyncratic position in the canon in terms of race, gender, and sexual orientation. She bestows new qualities on her trickster coming from the peripheries she dwells in and challenges the Jungian model. Through Afrekete’s linguistic dexterity and sexual identity, Lorde transforms the trickster from being seemingly innocuous into a figure of resistance grounded in lesbian erotica
Keywords: arts; discipline; personnes lesbiennes; ressource en ligne; sexualité; thématiques; érotisme; études littéraires